Factors Affecting the Use of Outplacement in the Banking Sectors of Poland and Russia = Czy outplacement jest bardziej popularny w Polsce niż w Rosji? Czynniki wpływające na popularność korzystania z outplacementu - Kaźmierczyk, Jerzy; Tarasova, Anna; Adrianova, Elena; Baszyński, Adam (Zielona Góra: Faculty of Economics and Management Press)
Outplacement is a rare HRM tool; hence there is also a lack of research on it. In turn, banks are treated as enterprises that implemented modern management solutions faster than other companies in the countries of Central and Eastern Europe. The bank is a good entity for outplacement testing. Both Poland and Russia belong to the CEE countries.
Keywords: outplacement; bank; Polska; Rosja; Poland; Russia